${LFIs}$ and methods of classical recapture. (27th November 2018) - Tajer, Diego
Abstract: In this paper, I will argue that Logics of Formal Inconsistency $(LFIs)$ can be used as very sophisticated and powerful methods of classical recapture. I will compare $LFIs$ with the well-known non-monotonic logics by Batens (2001, Log. Anal., 45–68) and Priest (2006, In Contradiction, Oxford University) and the 'shrieking' rules of Beall (2013, Rev. Symb. Log., 6, 755–764). I will show that these proposals can be represented in $LFIs$ and that $LFIs$ give room to more complex and varied recapturing strategies.